ANALYSIS OF FACTORS AFFECTING THE EXPORT OF NATURAL RUBBER PT. PERKEBUNAN NUSANTARA IX CENTRAL JAVA TO INDIA - Iwan Aminudin; Puspi Eko Wiranthi; Hilman Kurniawan (AGRIBUSINESS JOURNAL, 2021)
India is a consistent country to import PTPN IX natural rubber. Natural rubber production can export as much as 40.31% of PTPN IX natural rubber to India. The high export of natural rubber of PTPN IX and the lower production due to land conversion. PTPN IX natural rubber prices experienced a growth of 1.3% - 1.6%. PTPN IX's natural rubber exports to India reached 20,761,038 kg, with a total sales price of 238,415 million US$ per Kg. High exports of PTPN IX natural rubber to India in 2007-2017, research is needed on the factors affecting PTPN IX's natural rubber exports to India. The analysis method in this study is a quantitative model by compiling a system model of multiple regression equations, with Eviews version 11. The results showed that PTPN IX's natural rubber exports to India were influenced by the selling price of PTPN IX natural rubber, PTPN IX's natural rubber production volume, Indonesia's natural rubber price, and world synthetic rubber prices, while the world natural rubber price and Thailand's natural rubber price had no effect on PTPN IX's natural rubber exports to India. Meanwhile, the signification value of PTPN IX natural rubber exports to India is influenced by the price of PTPN IX natural rubber, world natural rubber prices, and world synthetic rubber prices, and has no significant effect, namely production volume, Indonesian natural rubber prices, and Thai natural rubber prices.